Pengaruh Kemudahan dan Keyakinan Penggunaan Sistem Informasi Baru terhadap Minat Pemanfaatan Sistem Informasi Pada Organisasi Perangkat Daerah Provinsi Riau - Fachroh Fiddin; Emma Dormos (Politeknik Negeri Bengkalis, 2019)
This research is to examine the effect of user convenience in using information systems and user confidence in using new information systems on the interest in using information systems. Respondents from this study are state civil servants who use information systems to complete their work. The data used is the perception of individual users of information systems in the Regional Government Organizations of the Riau Province Government with 144 respondents. The results showed that the ease of users in using information systems and user confidence in using new information systems have a significant influence on the interest in using information systems.